Adhalin Deficiency in Muscular Dystrophy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
A 13-year-old boy previously diagnosed with Becker's muscular dystrophy and dilated cardiomyopathy was studied at the University of Wisconsin, Madison, and the University of Iowa College of Medicine, Iowa City, and was found to have a deficiency of the dystrophin-associated glycoprotein, adhalin.